Website Design at SDN Cipete Utara 07 - Mardiani, Eri; Rahmansyah, Nur; Kurniati, Ira (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
The easiest way to introduce information to the public is to use technological developments, currently technology is a part of everyday life. Technology is needed in all fields, one of which is in the field of education, for the information society education is needed to know the condition of education in Indonesia, because education is a very important factor for society to increase intelligence, other factors with the use of technology are the most important. much needed by using technological facilities utilizing both desktop and web-based applications can help human activities. so in the world of education also keep abreast of developments, because of current demands that require society to better understand technological developments, schools need to continue to innovate in improving services and more comprehensive interaction with student guardians in particular and society in general. One of them is by utilizing internet media (school website). Departing from these needs, schools need to have media that can be used as a means of interaction between the school and the community and as a means of school existence in cyberspace, and to introduce schools to the community, schools must also be able to provide facilities that are easily known, one of which is using website. With a website, more information about the school can be provided to the public. In addition, the website also raises the status of the school.